2010
DOI: 10.1103/physrevd.82.103529
|View full text |Cite
|
Sign up to set email alerts
|

Modeling scale-dependent bias on the baryonic acoustic scale with the statistics of peaks of Gaussian random fields

Abstract: Models of galaxy and halo clustering commonly assume that the tracers can be treated as a continuous field locally biased with respect to the underlying mass distribution. In the peak model pioneered by Bardeen et al. (1986), one considers instead density maxima of the initial, Gaussian mass density field as an approximation to the formation site of virialized objects. In this paper, the peak model is extended in two ways to improve its predictive accuracy. Firstly, we derive the two-point correlation function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
221
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(243 citation statements)
references
References 138 publications
(297 reference statements)
18
221
3
Order By: Relevance
“…there is initial velocity bias, large scale gravitational evolution will naturally drive the galaxy velocity field to that of the dark matter [14,23]. On the other hand, the peak model predicts that the velocity bias persists and remains constant at late time [24]. This result seems to be favoured by the recent simulation results, which suggest that the halo velocity bias at late time is nonnegligible at k ∼ 0.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…there is initial velocity bias, large scale gravitational evolution will naturally drive the galaxy velocity field to that of the dark matter [14,23]. On the other hand, the peak model predicts that the velocity bias persists and remains constant at late time [24]. This result seems to be favoured by the recent simulation results, which suggest that the halo velocity bias at late time is nonnegligible at k ∼ 0.…”
Section: Introductionsupporting
confidence: 58%
“…these k 2 corrections can be derived from the peak model [26]. In [24], Zel'dovich approximation was used to displace the peaks to the Eulerian space, and they found that the velocity bias remains constant over time. The numerical measurement seemed to be in favour of the peak model result [15].…”
Section: Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…This approximation of scale-independent halo bias is valid to better than 10% on scales 20 < r < 130 h −1 Mpc (Manera & Gaztanaga 2011), with a small feature on the baryon acoustic scale (r ∼ 100 h −1 Mpc) of amplitude of 5% (Desjacques et al 2010). Throughout most of this paper we assume that correlations are negligible over cosmological distances (of order c/H 0 ), so that the redshift z on the right-hand side of Eq.…”
Section: Halo Mass Function and Correlationmentioning
confidence: 99%
“…To constrain primordial non-Gaussianity (PNG) from large-scale structure, we need to identify a signature that can be produced only by primordial non-Gaussianity and not by gravitational instability. One that has emerged in recent years is scale-dependent bias [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In this paper we investigate whether primordial non-Gaussianity leaves a distinctive imprint in a different arena, on the profile of dark matter halos.…”
Section: Introductionmentioning
confidence: 99%